2013
DOI: 10.1007/s00424-013-1374-1
|View full text |Cite
|
Sign up to set email alerts
|

Enteric sensory neurons communicate with interstitial cells of Cajal to affect pacemaker activity in the small intestine

Abstract: Enteric sensory neurons (the AH neurons) play a role in control of gastrointestinal motor activity; AH neuron activation has been proposed to change propulsion into segmentation. We sought to find a mechanism underlying this phenomenon. We formulated the hypothesis that AH neurons increase local ICC-MP (interstitial cells of Cajal associated with the myenteric plexus) pacemaker frequency to disrupt peristalsis and promote absorption. To that end, we sought structural and physiological evidence for communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…; Zhu et al . , ). In physiological conditions, a stimulus is most likely to be experienced locally and not to be uniform along the entire intestine.…”
Section: Resultsmentioning
confidence: 99%
“…; Zhu et al . , ). In physiological conditions, a stimulus is most likely to be experienced locally and not to be uniform along the entire intestine.…”
Section: Resultsmentioning
confidence: 99%
“…The gap junction contacts between ICC and smooth muscle cells make the ICC ideal to convey important information from the nerves to smooth muscle cells. Even in ICC with stimulus-independent slow-wave activity, the enteric nerves can modulate the pacemaker frequency (22,64). Hence, if the haustral boundary contractions have an ICC network as the origin of their rhythmicity, and if this pacemaker activity is dependent on neural excitation of the ICC, then the pacemaker activity will be abolished by TTX.…”
Section: Discussionmentioning
confidence: 98%
“…They are reported as being capable of spontaneously initiating electrical activity, which can be modulated by the stimulation of enteric nerves (Zhu et al, 2013); this process involves calcium transients (Yamashita, 2010). Cretoiu et al (2013) reported the existence of hyperpolarization-activated chloride-inward current with calcium dependence and the absence of L-type calcium channels in human myometrium.…”
Section: Our Hypothesismentioning
confidence: 99%